Eksistensi Prinsip Non-Refoulement sebagai Dasar Perlindungan Bagi Pengungsi di Indonesia Saat Pandemi Covid-19: Existence Of Non-Refoulement Principle As The Basis Of The Protection For Refugees In Indonesia During The Covid-19 Pandemic - Fathul Hamdani; Ana Fauzia (CV Rewang Rencang, 2021)
The presence of the principle of Non-Refoulement as an instrument in international law requires every country to provide protection for refugees or asylum seekers. However, during the Covid-19 pandemic, there are so many countries that have banned or refused refugees to enter their country in order to prevent the spread of Covid-19. The purpose of this study is to see how the Non-Refoulement principle exists as the customary of international law, and how the Non-Refoulement principle exists as a basis for protection for refugees in Indonesia. The results of the research show that there are problems related to the rights of refugees in Indonesia. However, it can be concluded that Indonesia has consistently applied this principle, for example when dealing with the exodus of Vietnamese refugees.